ANALYSIS OF SUSTAINABLE ECONOMICS IN LEMBANG FAULT DISASTER-PRONE AREAS, INDONESIA - Raden Aswin Rahadi; Alfita Puspa Handayani; Aqila Ayu Prasetyaningrum (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The geographical condition of Indonesia, at the confluence of three tectonic plates, results in the production of faults that can be found throughout the country, including the Lembang Fault. As a result of this state, the majority of the Lembang Fault area and its surroundings are disaster-prone, making the issue of economic resilience in disaster-prone areas crucial. Focus of ​​this research covers the villages traversed by the Lembang Fault. Over the past ten years, the economic growth in the region has been rather significant, particularly in eco and green tourism. The objective of this study was to obtain a map of the level of economic activity to determine economic activity in the Lembang Fault-prone area and a map of economic development recommendation areas in the Lembang Fault area. The methodologies used are literature review, sample data collecting through public questionnaires, and secondary data gathering in hotel, restaurant, and tourism data. The outputs obtained from this study are a thematic map of economic activity and a thematic map of regional recommendations for economic development in the Lembang Fault area. According to the findings, areas in the east (Bandung Barat Regency and Bandung Regency) with high and medium disaster risk values that are overlaid on low economic activity density values are the areas that allow for sustainable economic development. In the case of most high-risk overlay areas, further review on the preparation of mitigation and optimal community suppression is required in the event of an earthquake disaster caused by the Lembang Fault.